Conservation issues of historical public spaces on the example of transformations of the Old Town urban landscape in Bydgoszcz - Zimna-Kawecka, Karolina (Protection of Cultural Heritage, 2023)
The article is to present conclusions from the analysis of the conservation issues of selected transformations of the historic Old Town area of Bydgoszcz in the context of the principles of international doctrines regarding the protection of historic cities. Activities within the team in the field of revalorisation, revitalization and reconstruction have been lasting permanently since the late 1940s and very well illustrate the changes in the approach and adoption of planning and other solutions of functional, spatial and architectural concepts. Each public space is the result of decisions and expectations of various decision-makers and stakeholder groups. In the processes of preservation and development of historical areas, the guidelines of conservation officers were and are important, which have always been required not only to take care of monuments, implement the principles of conservation theory, but also to take into account the needs of the present. The reviewer of the activities is the society, which rarely formulates unanimous assessments, often without detailed knowledge about the circumstances of the creation or modification of the projects. The evaluation of the projects often requires an appropriate time perspective. The phases of reconstruction of historic cities in the 21st century, listed in the literature, are becoming blurred – there is an approach based on creative individualism with simultaneously undertaken reconstruction or modernist activities, which should result from an evaluative study and research. Recommendations from doctrinal documents, however, are often treated selectively by the authorities. Indications for conducting social consultations, creating interdisciplinary opinion-forming bodies, identifying the traditions of the city and creating local legal solutions are eagerly used. These regulations support conservation activities at the general level (e.g shaping the content of the local development plan). Unfortunately, in the complexes of buildings from the beginning of the 20th century, ordinary people, outside the conservation community, still do not have a sufficient understanding of the importance of preserving the authentic material or the functional and spatial arrangement. Investors point to the superiority of adaptation to a new function over the preservation of the historical matter/spatial arrangement, and they positively refer mostly to the reconstruction of the form as a reference to the tradition of the place. Protection and preservation of historic cities currently includes monitoring and management of social processes, where strictly conservation tasks are an element of management policy. The role of the conservator, who as an authority is responsible for the substantive protection of the monument, should be specified. Meanwhile, he is expected to make decisions based on factors outside this scope: pro-ecological or pro-economic, as supporting sustainable development.